2014
DOI: 10.1111/jfb.12299
|View full text |Cite
|
Sign up to set email alerts
|

Genetic evidence and new morphometric data as essential tools to identify the Patagonian seahorse Hippocampus patagonicus (Pisces, Syngnathidae)

Abstract: A genetic study to support morphometric analyses was used to improve the description and validate the Patagonian seahorse Hippocampus patagonicus (Syngnathidae) on the basis of a large number of specimens collected in the type locality (San Antonio Bay, Patagonia, Argentina). DNA sequence data (from the cytochrome b region of the mitochondrial genome) were used to differentiate this species from its relatives cited for the west Atlantic Ocean. Both phylogenetic and genetic distance analyses supported the hypot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
36
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(43 citation statements)
references
References 20 publications
(31 reference statements)
6
36
0
1
Order By: Relevance
“…After capture, individuals were fixed in 70% ethanol and deposited in the fish collection of the Capão da Imbuia Natural History Museum (MHNCI 12651). González et al (2014) and Silveira et al (2014) (Figure 2), and counts and measurements were consistent with those reported by these authors ( Table 2). Most of the characters provided by Piacentino and Luzzatto (2004) Silveira et al (2014) and González et al (2014).…”
Section: Pereira Et Al | New Records Of Hippocampus Patagonicus Fromsupporting
confidence: 81%
See 4 more Smart Citations
“…After capture, individuals were fixed in 70% ethanol and deposited in the fish collection of the Capão da Imbuia Natural History Museum (MHNCI 12651). González et al (2014) and Silveira et al (2014) (Figure 2), and counts and measurements were consistent with those reported by these authors ( Table 2). Most of the characters provided by Piacentino and Luzzatto (2004) Silveira et al (2014) and González et al (2014).…”
Section: Pereira Et Al | New Records Of Hippocampus Patagonicus Fromsupporting
confidence: 81%
“…González et al (2014) and Silveira et al (2014) (Figure 2), and counts and measurements were consistent with those reported by these authors ( Table 2). Most of the characters provided by Piacentino and Luzzatto (2004) Silveira et al (2014) and González et al (2014). The seahorse H. patagonicus seems to have a limited and uneven distribution in Brazil, known only from a few records from the states of Pernambuco, Rio de Janeiro, São Paulo, Paraná, Santa Catarina and Rio Grande do Sul (Anderson et al 2015, Silveira et al 2014; present study).…”
Section: Pereira Et Al | New Records Of Hippocampus Patagonicus Fromsupporting
confidence: 81%
See 3 more Smart Citations